2023
DOI: 10.1128/spectrum.03141-22
|View full text |Cite
|
Sign up to set email alerts
|

DivIVA Phosphorylation Affects Its Dynamics and Cell Cycle in Radioresistant Deinococcus radiodurans

Abstract: Deinococcus radiodurans , a radioresistant bacterium, lacks LexA/RecA-mediated DNA damage response and cell cycle regulation as known in other bacteria. However, it adjusts its transcriptome and proteome upon DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Cells expressing phosphor-mimetic mutants of FtsZ behaved differently than cells expressing phosphor-ablative and wild type, indicating the arrest of FtsZ function upon phosphorylation by RqkA ( Chaudhary et al, 2023a ). Furthermore, DivIVA phosphorylation at the T19 site had altered its typical pattern of localization near the new septum site and completely distorted its ability to determine the plane of the next division that is normally perpendicular to the previous plane of cell division ( Chaudhary et al, 2023b ) The enhancement of DNA repair function with the concurrent arrest of cell division upon Ser/Thr phosphorylation by RqkA nearly mimics these processes upon DNA damage as observed in eukaryotes ( Sancar et al, 2004 ). Thus, a possibility of RqkA role in DNA damage response and cell cycle regulation in this bacterium, nearly similar to the Ser/Thr protein kinase (STPK) in eukaryotes (eSTPK) roles in eukaryotes, could be hypothesized.…”
Section: Deinococcus Radiodurans Encodes Putative Substrate ...mentioning
confidence: 99%
“…Cells expressing phosphor-mimetic mutants of FtsZ behaved differently than cells expressing phosphor-ablative and wild type, indicating the arrest of FtsZ function upon phosphorylation by RqkA ( Chaudhary et al, 2023a ). Furthermore, DivIVA phosphorylation at the T19 site had altered its typical pattern of localization near the new septum site and completely distorted its ability to determine the plane of the next division that is normally perpendicular to the previous plane of cell division ( Chaudhary et al, 2023b ) The enhancement of DNA repair function with the concurrent arrest of cell division upon Ser/Thr phosphorylation by RqkA nearly mimics these processes upon DNA damage as observed in eukaryotes ( Sancar et al, 2004 ). Thus, a possibility of RqkA role in DNA damage response and cell cycle regulation in this bacterium, nearly similar to the Ser/Thr protein kinase (STPK) in eukaryotes (eSTPK) roles in eukaryotes, could be hypothesized.…”
Section: Deinococcus Radiodurans Encodes Putative Substrate ...mentioning
confidence: 99%
“…Deinococcus have also been reported to stop cell division in response to radiation stress; however, the exact mechanism of cell division arrest is not yet fully understood. Recent studies suggested that the phosphorylation of key cell division proteins such as FtsZ or DivIVA by the Serine/Threonine protein kinases (STPKs) (e.g., RqkA) could result in cell cycle arrest under radiation stress in D. radiodurans ( Chaudhary et al, 2023a ; Chaudhary et al, 2023b ). Importantly, both the Deinococcus strain (Ant6 and R1) contains large number of STPK but these proteins were not detected in the radioresistance strain K12 ( Supplementary Table S7 ).…”
Section: Interpretation Of Data Setmentioning
confidence: 99%
“…antioxidants protection [31,38,, novel DNA repair proteins [64][65][66][67][68][69][70][71][72][73][74][75], cellular signaling constitute serine/ threonine kinase and cell division regulation [47,[76][77][78][79][80][81][82][83][84][85][86][87][88][89], and a compact nucleoid structure [64,88,90,91], all working together to ensure cell survival after exposure to extremely high doses of gamma rays, prolonged desiccation, and other DNA damaging agents. Additionally, D. radiodurans maintains its competency throughout the exponential growth phase, experiencing a decline in transforming frequency only during the stationary phase [92].…”
Section: Introductionmentioning
confidence: 99%